2020
DOI: 10.1186/s12884-020-2798-1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal coffee intake and the risk of bleeding in early pregnancy: a cross-sectional analysis

Abstract: Background: Caffeine can easily cross the placenta, and maternal caffeine intake, thus, has an effect on fetal growth. However, it is still unclear whether coffee consumption is an independent risk factor for bleeding in early pregnancy. The objective of this study was to examine the association between pre-pregnancy coffee consumption patterns and the risk of bleeding in early pregnancy. Methods:A cross-sectional analysis was conducted among 3510 pregnant women from the Korean Pregnancy Outcome Study who unde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
1
9
1
Order By: Relevance
“…This also happens in Asian pregnant women. Data from the Korean pregnant outcome study (KPOS) shows that before conception, 17% of women were moderate coffee drinkers (1cup/day) and 18% were heavy coffee drinkers ( 2 cups/day) [12]. It should be noted in our study that, from conception, chocolate is more consumed than tea, which was not happening in the preconception stage, and differs from the results of other European studies [7,28] where chocolate is slightly consumed during pregnancy.…”
Section: Comparison With Other Studiescontrasting
confidence: 80%
See 1 more Smart Citation
“…This also happens in Asian pregnant women. Data from the Korean pregnant outcome study (KPOS) shows that before conception, 17% of women were moderate coffee drinkers (1cup/day) and 18% were heavy coffee drinkers ( 2 cups/day) [12]. It should be noted in our study that, from conception, chocolate is more consumed than tea, which was not happening in the preconception stage, and differs from the results of other European studies [7,28] where chocolate is slightly consumed during pregnancy.…”
Section: Comparison With Other Studiescontrasting
confidence: 80%
“…Findings from observational studies and meta-analyses indicate that maternal caffeine consumption is reliably associated with miscarriage, stillbirth, low birth weight and/or small for gestational age, childhood acute leukemia and childhood overweight and obesity [10,11]. Recently, it has been associated in Korean pregnant women a higher risk of bleeding in early pregnancy among those with heavy coffee consumption (2 cups of coffee/day) before pregnancy [12].…”
Section: Introductionmentioning
confidence: 99%
“…Of the surveyed women, 63.0% estimated more than one cup of coffee per day during pregnancy as being harmless. Guidelines across the world are inconsistent in their recommendations regarding the amount of coffee intake during pregnancy [ 20 , 21 , 22 , 51 , 52 ]. Thus, the limited knowledge base on the safe amounts of coffee consumption during pregnancy may be a result of limited and inconsistent guidelines and recommendations [ 52 , 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results from another meta-analysis suggested a dose–response relationship between coffee consumption and the risk of pregnancy loss [ 19 ]. A recent study from Korea showed that even less than one cup of coffee (light coffee drinker) and one cup of coffee per day (moderate coffee drinker) during pregnancy are associated with a significantly increased risk of bleeding in early pregnancy [ 20 ]. Coffee intake above one cup per day during pregnancy was found to be associated with childhood acute myeloid leukemia [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among South Korean populations, maternal coffee intake has been associated with increased risk of early pregnancy bleeding [ 18 ] and the risk of abortions [ 19 ], while abnormal (underweight, overweight, or obese) pre-pregnancy body mass index (BMI) has been associated with increased risk of preterm birth, preeclampsia, cesarean section deliveries, and gestational diabetes [ 19 ]. Thus, we hypothesize that certain maternal nutritional behaviors, including coffee consumption, dieting, and the consumption of junk foods are associated with increased risk of birth defects and/or congenital abnormalities in our study population.…”
Section: Introductionmentioning
confidence: 99%